PENGGUNAAN TEKNOLOGI GADGET SEBAGAI MEDIA PEMBELAJARAN PADA ANAK USIA DINI DI RAUDHATUL ATFHAL AL-IKHLAS KOTA SINGKAWANG - Nurhayati Nurhayati; Aslan Aslan; Susilawati Susilawati (JIP: Jurnal Ilmu Pendidikan, 2023)
The development of technology and communication is currently very rapid. The development of technology and communication has had a huge impact on the world of education, not only adults who are familiar with this sophisticated technology and communication, but also influences the development and education of early childhood and one of them is gadgets. The purpose of this study was to obtain information about "Using Gadget Technology as Learning Media in Early Childhood at Raudhatul Athfal Al-Ikhlas, Singkawang City". This research is a qualitative research with a descriptive study type. In this study, the primary data were group B class teachers and the head of RA Al-Ikhlas Singkawang, while the secondary data were students and parents of group B class students. The interviews were structured with questions compiled and linked and developed with related literature. Based on the description that has been described about "Use of Gadget Technology as Learning Media in Early Childhood at Raudhatul Athfal Al-Ikhlas Singkawang City", the researcher draws the following conclusions: 1. The use of gadgets by teachers as learning media for Raudhatul Athfal Al-Ikhlas Singkawang's children is good. Both parents and teachers can choose a way to control young children in using gadgets, one of which is by using gadgets as learning media in RA. The use of gadgets to become learning media for early childhood certainly has many positive values that can be taken, namely a) Application of technological advances to support the educational process, b) Reducing the use of gadgets for things that are less useful for early childhood, c) Teaches the use of gadgets wisely, d) Providing an understanding of the functions and benefits of gadgets to early childhood. 2. Various negative impacts that arise when children use gadgets too often such as children becoming passive, lazy, rebellious, selfish, children often argue with their parents, disturbed health and do not want to establish social relationships with other people such as peers in their social environment. This impact arises because children too often use gadgets at home without being controlled by their parents and children who are addicted to using gadgets feel that gadgets are the most interesting thing besides playing with the people around them or their peers.